2018
DOI: 10.3390/pharmaceutics10030155
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Nanoparticulate Formulation of Sirolimus and Its Tablets

Abstract: Nanocrystallization and amorphization have proven to be two effective strategies to improve the bioavailability of water-insoluble drugs. The purpose of our work was to develop a nano-formulated tablet of sirolimus (SRL) for enhanced dissolution. Amorphous SRL nanocomposites were prepared using anti-solvent precipitation via a high-gravity rotating packed bed. Various factors that affect particle size and size distribution, such as excipients, rotating speed, antisolvent/solvent flow rate, were investigated. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Today, nanomaterials play one of the most important roles in the research and development of modern pharmaceutics [1,2,3]. New material processing procedures [4,5,6,7,8], combined with different kinds of raw materials [9,10,11,12,13] and novel innovative strategies for constructing functional products [14,15,16,17,18], are frequently introduced into this application field for providing efficacious drug delivery and enhancing the therapeutic effects of active pharmaceutical ingredients (APIs). Among them, electrohydrodynamic atomization (EHDA) is a popular technique for creating nanoproducts, which mainly includes electrospraying and electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…Today, nanomaterials play one of the most important roles in the research and development of modern pharmaceutics [1,2,3]. New material processing procedures [4,5,6,7,8], combined with different kinds of raw materials [9,10,11,12,13] and novel innovative strategies for constructing functional products [14,15,16,17,18], are frequently introduced into this application field for providing efficacious drug delivery and enhancing the therapeutic effects of active pharmaceutical ingredients (APIs). Among them, electrohydrodynamic atomization (EHDA) is a popular technique for creating nanoproducts, which mainly includes electrospraying and electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation procedure of nanoparticle samples and even the presence of other components such as Kodia-PC seems to slightly affect the melting transition of the polymeric material, being the melting peak for all nanoparticle samples more broadly, and shifted to the lowest temperature (54-55 • C) compared to the raw copolymer. Moreover, in the thermogram of drug-loaded samples, the peak related to the melting point of Rapa is absent, demonstrating that the drug entrapment in the polymeric-based nanoparticle sample showed a different state, such as an amorphous state or disordered-crystalline phase of molecular dispersion or solid solution within the polymer matrix, as other authors have recently reported for Rapa or other molecules [35][36][37]. The thermograms did not reveal any degradation of materials in the range of tested temperature.…”
Section: Thermal Analysismentioning
confidence: 62%
“…This demonstrated that the crystalline peaks of the dye nanoparticles were significantly weakened and became an almost amorphous state. It is assumed that poorly water-soluble particles in amorphous state usually exhibit a faster dissolution rate in aqueous solutions [30,31]. In addition, the wetting property of nanoparticles with water was also studied.…”
Section: Resultsmentioning
confidence: 99%